Teachers Perception on the Relationship between Job Satisfaction and the Other Job-Related Outcomes: A Field Study. - BAKAN, smail; ERSAHAN, Burcu; BUYUKBESE, Tuba; OKUMUS, M. Tuncer (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
This study aims to investigate the relationship between overall job satisfaction and the job-related outcomes consisting of work/family conflict, family/work conflict, role conflict, role ambiguity, workload, general stress, emotional exhaustion and employee turnover intention. Regarding this aim, the research hypotheses were developed and tested from the perspectives of teachers and education administrators working in the city of Kahramanmaras in Turkey. In order to gather the research data a survey is applied to 360 teachers and administrators selected from different school types. Results reveal that there are significant relationships and differences among participants' job satisfaction levels and their perceptions on the job-related outcomes studied.